2007
DOI: 10.1093/ajcn/86.5.1791
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of the relations among cognitive dietary restraint, subclinical ovulatory disturbances, physical activity, and bone mass in healthy young women

Abstract: Background: Cognitive dietary restraint (CDR) may mediate subclinical ovulatory disturbances, which may result in loss of bone mineral density (BMD). CDR is associated with greater physical activity, which may modify the effect of CDR and ovulatory disturbances on bone mass. Objective: We aimed to investigate the relations among CDR, ovulatory disturbances, and physical activity and their effect on BMD in healthy premenopausal women over a 2-y period. Design: In this prospective cohort study, key explanatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…However, overall, BMI was not significantly related to intake of any food component (see Table 5). Participants’ dietary restraint scores in this sample were comparable with scores for the restraint scale of the TFEQ reported in other recent studies (Waugh, Polivy, Ridout, & Hawker, 2007; Williamson et al, 2007). Dietary restraint was not significantly related to aggregate appeal ratings (r = −.12; p = .18) but was negatively related to appeal ratings for Energy-Dense Main Courses (r = −.21; p < .05), and Meats (r = −.18; p < .05).…”
Section: Resultssupporting
confidence: 85%
“…However, overall, BMI was not significantly related to intake of any food component (see Table 5). Participants’ dietary restraint scores in this sample were comparable with scores for the restraint scale of the TFEQ reported in other recent studies (Waugh, Polivy, Ridout, & Hawker, 2007; Williamson et al, 2007). Dietary restraint was not significantly related to aggregate appeal ratings (r = −.12; p = .18) but was negatively related to appeal ratings for Energy-Dense Main Courses (r = −.21; p < .05), and Meats (r = −.18; p < .05).…”
Section: Resultssupporting
confidence: 85%
“…It is possible that there may be a threshold for an effect of dietary restraint, such that in the current study we did not have enough women with very high scores (n =23 with high restraint) to detect an association between restraint and UFC or bone density. Studies similar to ours in sample size and characteristics that examined bone density over a spectrum of dietary restraint scores also reported no relationship with aBMD [40,41], although one study noted lower total body BMC with higher restraint in three out of four body weight groups [41]. In addition, two studies of teens and young women with high activity levels reported lower aBMD among those with high versus low dietary restraint [42,43], although the inclusion of women with oligo-amenorrhea in those studies complicates interpretation.…”
Section: Discussionsupporting
confidence: 68%
“…The rationale for testing in these women is unclear. Past research by our group and others suggests that physical inactivity during adolescence [20,21] and delayed menarche [22] may result in failure to attain optimal peak bone mass. In the current study, neither of these risk factors, nor any others, differed significantly in prevalence by menopausal status.…”
Section: Discussionmentioning
confidence: 83%